2010
DOI: 10.1001/archgenpsychiatry.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Antipsychotic Treatment on Cerebral Function in Drug-Naive First-Episode Schizophrenia Revealed by “Resting State” Functional Magnetic Resonance Imaging

et al.

Abstract: We demonstrate for the first time, to our knowledge, that widespread increased regional synchronous neural activity occurs after antipsychotic therapy, accompanied by decreased integration of function across widely distributed neural networks. These findings contribute to the understanding of the complex systems-level effects of antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
260
7
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(302 citation statements)
references
References 65 publications
30
260
7
5
Order By: Relevance
“…We tried to address this issue by testing for functional differences in relatives who, by definition, carry higher genetic risk for the disease but are not on antipsychotic medications. Two recent studies (54,90) noted decreased DMN connectivity within MPFC regions in drug-naive SZ patients, and their findings are consistent with our data. One of these studies (90) showed that bilateral prefrontal cortex, parietal, caudate, and superior temporal regions had increased regional connectivity 6 wk after antipsychotic treatment.…”
Section: Ica Derived Dmnssupporting
confidence: 93%
See 1 more Smart Citation
“…We tried to address this issue by testing for functional differences in relatives who, by definition, carry higher genetic risk for the disease but are not on antipsychotic medications. Two recent studies (54,90) noted decreased DMN connectivity within MPFC regions in drug-naive SZ patients, and their findings are consistent with our data. One of these studies (90) showed that bilateral prefrontal cortex, parietal, caudate, and superior temporal regions had increased regional connectivity 6 wk after antipsychotic treatment.…”
Section: Ica Derived Dmnssupporting
confidence: 93%
“…Ceramides (composed of sphingosines and fatty acids) regulate cellular differentiation, proliferation, and apoptosis. Recent research implicates abnormal sphingolipid metabolism through alterations in peripheral ceramide levels in first-episode SZ (90), and abnormal plasma ceramide levels are reported in affective disorders, mild cognitive impairment, and memory disturbances (87,91 Fig. 4.…”
Section: Ica Derived Dmnsmentioning
confidence: 99%
“…In addition, higher LFO magnitudes in the precuneus node of the DMN are associated with stronger negative connectivity between DMN and task-positive networks (Di et al, 2013). Schizophrenia-related LFO alterations reported in the literature (He et al, 2013;Hoptman et al, 2010;Huang et al, 2010;Lui et al, 2010;Turner et al, 2013;Yu et al, 2013Yu et al, , 2014, as well as findings from our study linking lower LFO regional magnitudes to poorer cognitive task performance, may therefore reflect dysfunction of an important mechanism for gating functional neural connectivity. This speculation is consistent with conceptual accounts of schizophrenia as a disease predominantly of network dysconnectivity (Andreasen, 1999;Friston, 1998).…”
Section: Discussionsupporting
confidence: 68%
“…Measures of LFO amplitude have received relatively little attention in the schizophrenia literature, despite demonstration of regionally specific LFO differences between schizophrenia patients and healthy controls (He et al, 2013;Hoptman et al, 2010;Huang et al, 2010;Lui et al, 2010;Turner et al, 2013;Yu et al, 2013Yu et al, , 2014. A large sample study from the multi-site fMRI Biomedical Informatics Network (FBIRN) (Turner et al, 2013) reported widespread regions of decreased fractional ALFF (fALFF) in schizophrenia, including posterior cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine receptor antagonist has been shown to reduce global and local network efficiency in healthy adult brains (Achard and Bullmore, 2007). After short-term antipsychotic treatment, first-episode schizophrenia patients showed decreased functional connectivity across brain regions compared with pretreatment (Lui et al, 2010). However, the patient groups in our study showed increased connectivity compared with healthy controls.…”
Section: Discussionmentioning
confidence: 45%